Use of Geometer's Sketchpad in the Malaysian mathematics classroom - Wong, Shu Ling (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
There is increasing use of technology in the teaching of mathematics. Of particular interest in this study is a dynamic geometry software aimed at enhancing students’ mathematical understanding and increasing instructional efficiency. In 2004, the Ministry of Education in Malaysia purchased the licence for Geometer’s Sketchpad (GSP), one of many dynamic geometry software, for nationwide use. This paper examines studies regarding the efficacy of GSP in the Malaysian mathematics classroom, and in particular, the teaching of geometry and graph functions. Generally, this tool has been found to be effective in improving students’ geometry skills and mathematics achievement. This paper also looks at reviews of teachers’ and students’ attitudes towards the integration of GSP in the teaching and learning of mathematics. Both teachers and students have displayed positive attitudes towards GSP. Nonetheless, teachers have admitted that they face challenges such as time constraint, inadequate professional training regarding the use of the GSP, as well as the lack of hardware support to bring out the optimum application of technology in their classrooms. As such, school administration and authorities are urged to provide training and maintenance support to create an environment that is conducive to the use of GSP in the teaching and learning of mathematics.